The role of muscle in disease-related malnutrition. Decalogue of Good Practices - García Almeida, José Manuel; Bascuñana Ambrós, Helena; Terrados, Nicolás; Sanz Barriuso, Rebeca; López Pedrosa, José María; Campos Gorgona, Nefertiti; de Luis Román, Daniel (Progress in Nutrition, 2018)
Introduction: Disease-related malnutrition (DRM) is a major problem in Western societies, and the consequences pose a high economic burden. DRM affects not only muscle mass but also muscle function. However, there are currently few tools and strategies to enable a proper assessment of muscle and estimate muscle loss associated with malnutrition. Objective: To highlight the current situation of deficiency in the assessment of muscle mass and function in malnourished patients and to develop recommendations for the inclusion of muscle assessment as an element of measurement in the nutritional recovery of patients with DRM. Methods: A multidisciplinary expert panel comprised of twenty-one physicians from Spain was convened to review, refine and summarize current recommendations on the assessment, diagnosis, and nutritional and functional treatment of malnourished patients. Results: The experts highlighted the impact of DRM on muscle, as well as the crucial role of this organ in the correct nutritional, metabolic and functional recovery of patients. The lack of strategies for the assessment of muscle in DRM led to a proposed Decalogue of Good Practices for the optimal treatment of these patients. Conclusion: The review is intended to guide in the nutritional and functional recovery of patients with DRM, based both on consensus opinions of experts and on the most recent scientific evidence in the field. The proposed Decalogue provides a comprehensive approach to the management of the malnourished patient.